BEHAVIORAL MODEL OF DATA BLOCK RECOVERY SYSTEM FOR THEIR REMOTE DISTRIBUTED STORAGE - ANTONIUK, Anton; KOLIADA, Kostiantyn (Herald of Khmelnytskyi National University. Technical sciences, 2022)
A behavioral model of the data block recovery system for their remote distributed storage has been developed. The model was created based on the method of data recovery during their distributed storage in remote storage. The used method allows for restoring information in case of its loss or damages it is possible to recover a completely lost data cluster, provided there are no errors on other clusters, or to recover up to three blocks of data on different clusters.According to the method used, the developed behavioral model provides the functionality of restoring information to the stated requirements. To create a behavioral model, the language of description of integrated circuit hardware was used, namely VHDL. The model provides 5 different devices that combine into one system. During the operation of the model, such functions are performed as solving several systems of equations, sorting, adding two vectors modulo, etc. Simplicity and speed of execution of these functions provide high potential efficiency of execution of the set algorithm.The feasibility of developing a model of this data recovery system is the possible future use of it in distributed storage systems. The advantage is that the model allows you to recover lost data unnoticed by the user, or a data cluster, computer, etc. because it is the developed system must first receive the data stream, identify it, analyze, and if there is no error - just pass it to the user, otherwise, recover data if possible. Data recovery requires the following: data, backup blocks, and a backup matrix, which was created during the initialization of the distributed storage network and stored in the memory of the developed system. In case of impossibility of data recovery, the developed system gives out the corresponding signal.
Keywords: VHDL; distributed data storage; data backup; data recovery